Phase transformation behavior of a Mn containing β-solidifying γ-TiAl alloy during continuous cooling. (August 2018) - Xu, Hao; Li, Xiaobing; Xing, Weiwei; Shu, Lei; Ma, Yingche; Liu, Kui
Abstract: The research was mainly focused on the phase transformation of Ti-42Al-5Mn (at%) alloy produced by vacuum induction melting (VIM) and vacuum arc remelting (VAR) followed by wrought process. The phase transformation kinetics of the alloy during continuous cooling under the cooling rates of 0.1 °C/s, 0.5 °C/s, 2 °C/s, 10 °C/s, 50 °C/s, and 200 °C/s were identified by the Gleeble-3800 system, which is finally used to construct a schematic continuous cooling transformation (CCT) diagram of this alloy. The related phase composition, microstructure and property of the alloy were studied using X-ray diffraction (XRD), electron probe micro analyzer (EPMA), transmission electron microscope (TEM) and Vickers hardness (HV). It shows that six kinds of phase transformation are existed during continuous cooling from 1300 °C with the cooling rates of 0.1 °C/s, 0.5 °C/s, 2 °C/s, 10 °C/s, 50 °C/s, 200 °C/s and WQ, including β→α2 ′, β→α, β→γ, β→βo /α→α2, α2 →α2 /γ and α2 /γ→βo, sec . It reveals that partial transformations would be inhibited when the cooling rate is relatively high. The martensitic structures (α2 ′) obtained by β→α2 ′ were formed under the WQ condition after holding at 1300 °C for 5min, and it will be completely restrained below the cooling rate of WQ. For the β→γ, it is restrained if the cooling rates are higher than 50 °C/s. The α2 →α2 /γ could be also suppressed when cooling with 200 °C/s, and the γ lath within the supersaturated α2 -grains would be formed at lower cooling rate below 50 °C/s. For 0.5 °C/s and 0.1 °C/s, a small amount of dotted βo (βo, sec ) phases can be formed in the lamellar interfaces, which is proved the reaction products of α2 /γ→βo, sec . Furthermore, the effect of cooling rates on the microstructure, including interlamellar spacing ( λ ) and γ grains are also identified and discussed. Graphical abstract: Image 1 Highlights: Five kinds of phase transformations including β→α, β→γ, β→βo /α→α2, α2 →α2 /γ and α2 /γ→βo, sec occur during our CCT test. This paper clarifies specific transformation temperature range of α2 →βo, sec for the wrought Ti-42Al-5Mn alloy. 5 at%Mn addition tends to decrease the increasing trend of interlamellar spacing with the cooling rate reducing.